Development of Mathematics Encyclopedia on Spatial Building for Fifth Grade Elementary School Students - Atminarsih Wulandari; Meita Fitrianawati (Jurnal Genesis Indonesia, 2023)
This study aims to develop a mathematics learning media called the Mathematics Encyclopedia for 5th-grade elementary school students, to determine the feasibility of this media in understanding the subject of spatial building in the 5th-grade curriculum. This research uses the Research and Development (RnD) method, utilizing the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The collected data are analyzed using qualitative and quantitative analysis methods. The results of the study are a mathematics encyclopedia book for spatial building materials, which has been validated by content experts, instructional experts, and media experts. The validation results indicate that the developed book is suitable for use in the learning process, with an overall assessment of "Very Good" to "Good." The book also received high praise from the mathematics teacher and the student respondents, indicating that it is suitable for use as a learning tool for 5th-grade students in elementary school.